Perbedaan Efektivitas Konsumsi Telur Ayam dan Ikan Gabus terhadap Penyembuhan Luka Perineum pada Ibu Nifas di Klinik Saswa Medika Tahun 2024 - Wiwit Desi Intarti; Friska Junita; Reza Viera Agnesia (Jurnal Kebidanan Harapan Ibu Pekalongan, 2025)
Perineal wounds in postpartum women can slow down the postpartum recovery process. Optimal wound care is needed to prevent infection and accelerate healing. Animal proteins such as chicken eggs and cork fish are known to have benefits in accelerating tissue regeneration. This study aims to determine the difference in the length of perineal wound healing between postpartum women who consume chicken eggs and those who consume cork fish at Saswa Medika Clinic in 2024. This study used a quasi-experimental design with a post-test only group design approach. The study sample consisted of 20 postpartum women who had perineal wounds, divided into two groups: a group that consumed chicken eggs and a group that consumed cork fish for 7 days. Wound healing was measured using the REEDA scale on days 4 and 7. Data analysis used Mann-Whitney test. The results showed that postpartum women who consumed cork fish experienced faster wound healing compared to those who consumed chicken eggs. The majority of mothers in the cork fish group had lower REEDA scores, indicating better wound condition than the chicken egg group (p < 0.05). Consumption of cork fish is more effective in accelerating perineal wound healing than chicken eggs. This study can be a reference for health workers in providing education about nutritional intake that supports the recovery of postpartum women.